Induction of memory cytotoxic T cells to influenza A virus and subsequent viral clearance is not modulated by PB1‐F2‐dependent inflammasome activation. Issue 5 (26th January 2016) - Lee, Patricia (Hoi Yee); Bird, Nicola; MacKenzie‐Kludas, Charley; Mansell, Ashley; Kedzierska, Katherine; Brown, Lorena; McAuley, Julie
Abstract : Expression of the viral virulence protein PB1‐F2 during infection has been linked to NLRP3 inflammasome complex activation in macrophages and induction of early inflammatory events enhancing immunopathology during influenza disease. We sought to determine whether PB1‐F2‐specific NLRP3 inflammasome activation influenced the magnitude and/or robustness of the CD8 + T‐cell responses specific for conserved viral antigens and subsequent virus elimination. Using murine heterosubtypic viral infection models, we showed that mice infected with virus unable to produce PB1‐F2 protein showed no deficit in the overall magnitude and functional memory responses of CD8 + T cells established during the effector phase compared with those infected with wild‐type PB1‐F2‐expressing virus and were equally capable of mounting robust recall responses. These data indicate that while expression of PB1‐F2 protein can induce inflammatory events, the capacity to generate memory CD8 + T cells specific for immunodominant viral epitopes remains uncompromised.